The relationship between macroeconomic variables and economic growth in Malaysia / Faznur Faizren Musa - Musa, Faznur Faizren (Faculty of Business and Management, 2014)
This paper aims at examining the relationship between macroeconomic variables, namely consumption expenditure (CE), foreign direct investment (FDI), government expenditure (GE), export (X), and exchange rate (ER) with the economic growth in Malaysia. Economic growth is the indicator in which we can see on how well and developed a country is. It can measure in terms of the gross domestic product (GDP). This study will focus on the economic growth in Malaysia. The sample of this study comprises of 30 observations each of the independent and dependent variables on a yearly basis over 30 years period from the year 1984 to 2013. The dependent variable for this study is gross domestic product as it represents economic growth and the independent variables are consumption expenditure, foreign direct investment, government expenditure, export and exchange rate. Methodology used for this study is by using E-view software. The findings and results of this research paper would provide us with an indicative view and could form an important basis for policy makers to promote economic growth.